Pelatihan Pemerataan Kepersertaan Jaminan Kesehatan Nasional Secara Online Di Wonolelo Pleret Bantul - Sri Sularsih Endartiwi (Poltekkes Kemenkes Denpasar, 2020)
Citizens of the Cegokan Wonolelo Pleret Bantul sub-village still do not understand the National Health Insurance (NHI) program managed by the BPJS. Public knowledge is still very minimal and the desire to register to become NHI participants is still low due to several factors such as the economy and information that is still minimal. The objective is the public can register to become a National Health Insurance participant online. Method by Counseling and training.Knowledge and ability of community participants about the ways and flow of registration to become participants in the National Health Insurance program increased after counseling and training from 40% to 95%. Community can practice registering for NHI online. Community knowledge and abilities are good about registering as participants in the National Health Insurance program after counseling and training.